EP485 Confounding factors of trans-vaginal ultrasonography accuracy in endometrial cancer. (1st November 2019) - Capozzi, VA; Gambino, G; Morganelli, G; Cianciolo, A; Pugliese, M; Sozzi, G; Armano, G; Monfardini, L; Gaiano, M; Ceni, V; Rolla, M; Merisio, C; et al.
Abstract : Introduction/Background: Endometrial cancer is the most frequently diagnosed gynecological tumor with more than 60.000 new cases each year. Following the ESMO-ESGO-ESTRO consensus conference, patients are classified in different classes of risk for lymph node metastases based on the instrumental suspected stage of the disease. In this scenario, a correct pre-operative workup is essential for a proper planning treatment offered to the patient. Although most of the oncological centers have replaced the MRI with trans-vaginal ultrasound, this, in the international guidelines, is considered only in the fertility sparing and in cases of contraindicated MRI. The Aim of our study is to evaluate the diagnostic accuracy of transvaginal ultrasonography in relation to confoundable factors that may affect its quality, to a proper patient risk stratification and a consequent better surgical strategy. Methodology: The study analyzed 290 patients with histological diagnosis of endometrial adenocarcinoma. Each patient was subjected to the anamnestic collection, chest/abdomen/pelvis CT, assessment of Ca-125 and transvaginal ultrasound. The tumor ultrasound description was made according to IETA terminology. According to the FIGO staging system, the depth of myometrial invasion was rated as superficial (M1, <50%) or deep (M2, >50%). Results: Of the 272 patients included in the study in 214 (78.7%), there was an agreement between the depth of ultrasound myometrial infiltration and definitive histological examination. The FIGO stage IB (figure 1) was the main statistically significant confounding factor in the univariate analysis about ultrasound myometrial infiltration diagnosis (p=0.004). Fibromatosis and/or adenomyosis was significantly associated with a discordant ultrasonographic diagnosis in univariate analysis (p=0.04). Conclusion: The study shows a high concordance between transvaginal ultrasonography and definitive histological examination in predicting myometrial infiltration, with 86, 8% sensitivity (CI: 81.1–91), 64.4% specificity. Myometrial infiltration over 50% (Figo stage IB) represents the main confounding factor. Disclosure: Nothing to disclose.